PKM JEJORONG CAKE PACKAGING LABELING DESIGN FOR UMKM IN PARIGI VILLAGE, CIKANDE DISTRICT, SERANG REGENCY - Muhammad Angga Anggriawan; Sari Putri Pertiwi; Evi Dora Sembiring; Muhamad Shidqi; Vani Khusnul Khotimah (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Cikande District is one of the industrial area areas in Serang Regency, Province. Parigi Village is one of 13 villages in Cikande District. As a village adjacent to an industrial area, of course, this has resulted in residents preferring a livelihood as laborers or factory employees. However, in Parigi village, Kukuh village to be precise, there is a traditional cake production business, namely Jejorong cake, which is also carried out in a traditional way. The goal to be achieved in this PKM is to provide assistance and education to UMKM in the household industry, namely Jejorong Traditional Cakes, which are in Parigi Village, Kampung Kukuh, Cikande District, so that they can develop and expand to a wider scale business through improving packaging labeling and business management. The outputs generated from the PKM program include two aspects, production aspects and management aspects. The methods used in this activity include: counseling about good product packaging so that it lasts longer and giving product names. This service was carried out for about one month in Parigi Village, Kampung Kukuh, Cikande District, for UMKM, traditional Jejorong cakes, Ibu Nanih. This program produces Jejorong Traditional Cakes with labeling packaging that has economic value so that it further increases the selling value of Jejorong cakes, and partners can find out how to manage business management from a financial point of view